Cities in precipice: on sensitive frontiers on and offline (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The authors present in this text a reflection on poetic and political forces involved in the theater scene immersed in the contingent evidenced by the pandemic of COVID-19. From the streets and theaters possible in this context, they aim to think about the cities that emerge for the time being in the imaginary experienced on the on and offline frontier, either by the processes of composition in art that were forced to migrate to the internet or by the ballast left by the media of communication in a hyperconnected world. Through the dialogue with Nestor Garcia Canclini and other thinkers of the contemporary scene, they note the fusion operated between what they call online cities and offline cities here to think about the poetic challenges that arise in the debates about time-space inside and outside the internet. What will be left of our theaters in the midst of an information pandemic? Defending an expansion of the sensitive, they leave the contemporary scene to think that other bodies and spatialities are being demanded or imposed in the midst of the turmoil of the biopolitical war that surrounds us.
Keywords: Online Cities; Offline cities; Contemporary theater; Internet